Spectral Energy Distribution Variability of the Blazar OJ 287 During 2009–2021 - Wenwen Zuo; Alok C. Gupta; Minfeng Gu; Mauri J. Valtonen; Svetlana G. Jorstad; Margo F. Aller; Anne Lähteenmäki; Sebastian Kiehlmann; Pankaj Kushwaha; Hugh D. Aller; Liang Chen; Anthony C. S. Readhead; et al. (The Astrophysical Journal)
Using nearly simultaneous radio, near-infrared, optical, and ultraviolet (UV) data collected since 2009, we constructed 106 spectral energy distributions (SEDs) of the blazar OJ 287. These SEDs are well fitted by a log-parabolic model. By classifying the data into “flare” and “quiescent” segments, we find that the median flux at the peak frequency of the SEDs during the flare segments is 0.37 ± 0.22 dex higher compared to the quiescent segments, while no significant differences are observed in the median values of the curvature parameter b or the peak frequency $logν {\rm{p}}$ . A significant bluer-when-brighter trend is confirmed through the relation between the V magnitude and B − V color index, with this trend being stronger in the flare segments. Additionally, a significant anticorrelation is detected between $logν {\rm{p}}$ and b , with a slope of 5.79 in the relation between 1/ b and $logν {\rm{p}}$ , closer to the prediction from a statistical acceleration model than a stochastic acceleration interpretation, though a notable discrepancy persists. This discrepancy indicates that additional factors—such as deviations from idealized conditions or radiative contributions, such as the thermal emission from the accretion disk in the optical–UV range during quiescent states—may play a role in producing the observed steeper slope. Within the framework of the statistical acceleration mechanism, the lack of correlation between the change in the peak intensity and the change in the peak frequency suggests that the change in the electron energy distribution is unlikely to be responsible for the time-dependent SED changes. Instead, changes in Doppler boosting or magnetic fields may have a greater influence.